2017
DOI: 10.1016/j.juro.2016.09.073
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to National Comprehensive Cancer Network® Guidelines for Testicular Cancer

Abstract: Nonguideline directed care of patients with testicular cancer is common, most frequently in the form of inappropriate imaging and overtreatment. Nonguideline directed care leads to delayed definitive therapy, unnecessary morbidity and higher rates of relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 27 publications
1
30
0
4
Order By: Relevance
“…The cohorts were well matched and proportions of the IGCCCG risk groups were consistent with the literature (Table 1) [14,26]. All patients with metastatic disease received cisplatin based chemotherapy.…”
Section: Resultssupporting
confidence: 53%
“…The cohorts were well matched and proportions of the IGCCCG risk groups were consistent with the literature (Table 1) [14,26]. All patients with metastatic disease received cisplatin based chemotherapy.…”
Section: Resultssupporting
confidence: 53%
“…Testicular germ-cell tumors (TGCTs) remain the most common solid neoplasms among young men aged 20-40 yr, with an incidence of 3-10 cases per 100 000 men in industrialized countries [1]. Although the cure rate even among patients with extensive metastatic disease is still excellent owing to the high chemosensitivity of TGCT, a multidisciplinary approach and strict adherence to guidelines are mandatory to achieve and maintain excellent treatment results [2,3]. These recommendations are underlined by a recently published study demonstrating that approximately one-fifth of all patients receive a nonguideline-recommended treatment [4] leading to significantly lower relapse-free survival in comparison to guideline-concordant management (p = 0.005).…”
Section: Introductionmentioning
confidence: 99%
“…For initial staging, chest CT and abdominal CT were correctly utilised by >80% of urologists. Our guideline compliance rates were significantly improved as compared with a previous study that retrospectively analysed 593 TC patients and found an inappropriate imaging rate of 44% with respect to the NCCN guidelines (Wymer et al, 2017). A French survey of 289 urologists revealed a guideline adherence rate of 66% for the initial radiological workup (Rigaud et al, 2014).…”
Section: Discussionmentioning
confidence: 53%
“…For optimal staging, treatment and follow‐up, it is essential to utilise current guidelines (Albers et al, ; Motzer et al, ). A previous study showed that non‐guideline‐directed care led to inappropriate imaging (44%), overtreatment (40%) and misdiagnosis (24%) (Wymer et al, ). Additional studies have found insufficient post‐treatment imaging rates and unnecessary adjuvant therapy regimens when compared with current guideline recommendations (Matulewicz, Oberlin, Sheinfeld, & Meeks, ; Rusner, Stang, Dieckmann, & Friedel, ).…”
Section: Introductionmentioning
confidence: 99%